Literasi Akademik Mahasiswa Calon Guru IPA Di Era Artificial Intelligence: Analisis Kebutuhan Pengembangan Model Pembelajaran Berbasis AI - Rifda Nur Hikmahwati Arif; Salma Samputri (JAMBURA Elementary Education Journal, 2025)
The integration of Artificial Intelligence (AI) in higher education offers new opportunities as well as challenges for developing students’ academic literacy. This study aimed to identify: (1) patterns of AI use in learning among pre-service science teachers; (2) challenges in writing scientific articles; (3) the level of understanding of AI-assisted content; (4) intellectual independence in writing without AI; and (5) students’ needs for innovation in learning models. A quantitative descriptive survey was conducted with 86 Science Education students at Universitas Negeri Makassar selected purposively. Data were collected using a validated 35-item questionnaire (α=0.89) and analyzed using descriptive statistics. Results showed that 100% of students used AI for academic tasks, with ChatGPT as the dominant application (57,1%). Major challenges included writing articles using the IMRAD structure (33,3%), understanding research methodology (15,9%), critical thinking (15,9%), deep understanding of AI outputs (23,8%), and independent writing without AI (9,5%). Moreover, 76,1% of students reported the need for a systematic learning model that integrates AI with effective pedagogy. These findings indicate that although AI has been widely adopted, its use is not yet optimal and may foster counterproductive dependence in academic literacy development. The study recommends developing an innovative learning model that positions AI as a cognitive scaffold grounded in constructivist pedagogy, gradual mentoring, and critical AI literacy.